Diagnostic value of serum primary bile acids in detecting bile acid malabsorption. Issue 10 (October 1982) - Aldini, R; Roda, A; Festi, D; Mazzella, G; Morselli, A M; Sama, C; Roda, E; Scopinaro, N; Barbara, L
Abstract : Serum cholic and chenodeoxycholic acid conjugates were measured in fasting conditions and after meals in 14 patients with bile acid malabsorption due to ileal resection. Mean serum fasting levels of both primary bile acids did not differ from the controls. After meals, serum cholic acid peaks were lower in patients with ileal resection than in control subjects (p less than 0.001), while chenodeoxycholic acid peaks were reduced in colectomised patients (p less than 0.01). In the sera from patients with ileal resection, the glycine/glycine + taurine ratio for cholic and chenodeoxycholic acid increased (p less than 0.001) from morning to evening, and glycine/glycine + taurine ratio for chenodeoxycholic acid was significantly (p less than 0.01) different from the controls in the sera collected in the evening. The results are consistent with the concept of a better intestinal conservation of chenyl, mainly of the glycine conjugated from, than of cholylconjugates, in patients with ileal resection; this is probably because of passive absorption in the intestine. The postprandial peaks of serum cholic acid conjugates may therefore be regarded as a test of ileal dysfunction, while peaks of chenodeoxycholic acid conjugates suggest colonic impairment.